SOSIALISASI PENGELOLAAN SAMPAH ORGANIK DAN NON ORGANIK DI DESA MEDALEM KECAMATAN TULANGAN-KABUPATEN SIDOARJO - Ardhana Rahmayanti; Laily Noer Hamidah; Atik Widiyanti; Muchammad Tamyiz (Journal of Science and Social Development, 2018)
Waste has become material considered useless anymore. The rate of waste generation continually increase along with the increase of population, making it increasingly threaten the environment. This situation has been exacerbated by the poor handling of the government and society towards waste. Management of waste sources has become an alternative that can be used to handle the waste problem. The community service program has been carried out in the village of Medalem, Tulangan, Sidoarjo to overcome the occurring of waste problem. The public understanding and awareness of waste issues has been improved through the explanation of material, direct practice and the discussion how to process and sort the household waste. The material that has been explained, includes the waste, the classification of the waste based on its nature, and how to manage waste. It was found out that the Community Service program has improved the public understanding of waste, it was shown that more than 65% of participants had answered the questions correctly. The results of the analysis showed that the public attitude and behavior towards waste problems was good. It was supported by the presence of waste facilities that have been provided by the Village Devices.